PENGARUH LINGKUP CORPORATE SOSIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK (Studi Empiris pada Perusahaan Non Keuangan yang terdaftar di Bursa Efek Indonesia Tahun 2016-2018) - Wuri Ismail; Herry Laksito (Diponegoro Journal of Accounting, 2020)
This study aims to investigate the relationship between dimensions of corporate social responsibility and tax aggressiveness. The independent variables in this research are environmental dimension of CSR, social dimension of CSR and governance dimension of CSR. While the dependent variable used in this study is tax aggressiveness.This study uses secondary data from the financial information provided on Bloomberg database of companies listed on the Indonesian Stock Exchange. Seventy-eight samples were selected using the purposive sampling method in non-financial industry, which published its financial statements during the years 2016 to 2018. Multiple regression analysis is the test used to analyze the relationship environmental dimension of CSR, social dimension of CSR, and governance dimension of CSR on tax aggressiveness. The result of this research  shows that second hypothesis with variable social dimension of CSR was accepted. Social dimension of CSR has negative significant influence on tax aggressiveness. Meanwhile first and third hypothesis with variable governance dimension of CSR and environmental dimension of CSR was rejected because it has the opposite direction with result. Governance dimension of CSR have negative significant influence on tax aggressiveness and environmental dimension of CSR positive significant influence on tax aggressiveness.